2016
DOI: 10.1016/j.ijscr.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Primary angiosarcoma of the breast

Abstract: Primary angiosarcoma (AS) of the breast is a rare neoplasia that is not related to radiation exposure. It represents less than 0.05% of all malignant breast tumors. This lesion is characterized by aggressive patterns and poor prognosis and by the absence of typical features at radiologic examination.Currently there are not evidence-based guidelines regarding surgical and adjuvant treatment for this tumor even though wide surgical resection followed by chemo- radiotherapy appears to improve both disease free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 30 publications
3
41
0
3
Order By: Relevance
“…These findings represent the typical clinical presentation cited in the literature for both types [3], [6].…”
Section: Discussionsupporting
confidence: 82%
“…These findings represent the typical clinical presentation cited in the literature for both types [3], [6].…”
Section: Discussionsupporting
confidence: 82%
“…No entanto, o estudo justificou essa aparente falta de benefício como provavelmente resultado do pequeno tamanho da amostra e do viés de seleção do paciente. Devido a atividade da quimioterapia citotóxica no angiossarcoma metastático da mama, essa modalidade terapêutica certamente deve ser considerada em pacientes com angiossarcoma mamário localizado de alto risco, e os regimes de quimioterapia com antraciclinaifosfamida e gemcitabina-taxano parecem ser altamente ativos (Sher et al, 2007) A radioterapia Research, Society and Development, v. 9, n. 3, e179932654, 2020(CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i3.2654 adjuvante após a cirurgia pode ter um efeito benéfico nos sarcomas mamários, principalmente em pacientes com margens microscopicamente positivas (Bordoni et al, 2016). O prognóstico do angiossarcoma da mama, como cada histotipo de sarcoma, está relacionado ao tamanho do tumor, ao grau do tumor e ao status da margem de ressecção (Bordoni et al, 2016).Geralmente, trata-se de um prognóstico ruim pois apresenta risco moderado de recorrência local e alto risco de metástase (Bousquet et al, 2007 ) No caso aqui relatado, apesar de não ter sido possível a avaliação das margens cirúrgicas e de não ser um grau tão desfavorável quanto o tipo III, trata-se de um caso de difícil manejo devido ao tamanho do tumor apresentado e, principalmente, a presença de metástases que acabaram por reduzir drasticamente a expectativa de sobrevida dessa paciente.…”
Section: Discussionunclassified
“…(5) In general, chemotherapy regimen is chosen empirically due to the rarity of the disease and lack of definite standardized treatment. Some studies (5,9) have suggested that treatment with anthracyclin-based chemotherapy, with either doxorubicin, or epirubicin with ifosfamide may improve both disease-free DFS and overall survival (OS). Systemic chemotherapy and re-irradiation are indicated only in RASB patients with local and/or systemic recurrences.…”
Section: ❚ Discussionmentioning
confidence: 99%